Development of nutrient cycle through agricultural activities of a rural area in the North of Vietnam - Do Thu Nga; Ta Thi Tha; Vu Van Tu; Phuc Pham Duc; Hung Nguyen-Viet (Springer, 2018)
Material flow analysis (MFA) has been applied to assess the environmental impact of human activities on nutrient flows at the commune scale. This paper reports the assessment of human excreta and animal manure as a nutrient source for paddy fields and fishponds in Hoang Tay commune, Ha Nam province, Vietnam. The quality of MFA model was confirmed through modified uncertainty analysis, then was used to originally quantify and visualize the interlinks of livestock with the environmental sanitation and agricultural system in terms of nutrients. Currently, half of the pig manure was collected to the biogas, and the remainders were freely discharged to the commune’s drainage system (25%) or directly reused in the paddy fields (25%). While wastewater in the drainage system was the biggest source of nitrogen (contributed 46%), paddy field was the biggest source of phosphorous (contributed 55%) discharged to the Nhue River, totaling 57 ± 9 ton N and 29 ± 6 ton P, annually. Consequently, mitigation measures for nutrient resource management were proposed, and reducing half of chemical fertilizers applied and reusing all excreta and manure in the paddy fields were the most effective option.